Colloidally stable polypeptide-based nanogel: Study of enzyme-mediated nanogelation in inverse miniemulsion - Dvorakova, Jana; Salek, Petr; Korecká, Lucie; Pavlova, Ewa; Cernoch, Peter; Janouskova, Olga; Koutnikova, Barbora; Proks, Vladimir (Wiley-Blackwell, 2019)
The current work presents a pivotal study of the nanogelation of the linear poly(N-5-2-hydroxypropyl-L-glutamine) polymer precursor containing tyramine (TYR) units in an inverse miniemulsion by horseradish peroxidase/H2O2-mediated crosslinking. The effects of various n(H2O2)/n(TYR) ratios on the kinetics of nanogelation in the inverse miniemulsion and on the reaction time are investigated by linear sweep voltammetry, while the formation of dityramine crosslinking is explored by fluorescence spectroscopy. The study is completed using dynamic light scattering measurements, nanoparticle tracking analysis, and cryogenic transmission electron microscopy to acquire comprehensive information about the formed nanoparticulate systems. With the optimal ratio n(H2O2)/n(TYR) = 2, the strategy yields in the high-quality 130 nm poly(amino acid)-based nanogel, which is prepared in 2 h. The nanogel is colloidally stable under different temperature and pH conditions for over 168 h. Moreover, the demonstrated nanogel is noncytotoxic for HeLa cells and human primary fibroblasts and is quickly enzymatically hydrolyzed into small fragments during a biodegradation study in human blood plasma. (c) 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 137, 48725.
Koloidálně stabilní polypeptidové nanogely: Studie enzymem-zprostředkované nanogelace v inverzní miniemulzi
Keywords: biodegradable; biomedical applications; colloids; crosslinking; synthesis and processing techniques; biodegradabilní; biomedicínské aplikace; koloidy; síťování; snytéza a procesní techniky